The burden of German history a transatlantic life - Jarausch, Konrad 1941- (Berghahn, 2023)
"As one of the leading historians of the post-1956 generation and an internationally acclaimed scholar for the past five decades, Konrad H. Jarausch's autobiography presents a sustained academic reflection on the post-war German effort to cope with the guilt of the Holocaust amongst a generation of historians too young to have been perpetrators. Ranging from his war-time childhood in a chaotic country, to Americanization as a foreign student, and concluding with his mentorship of PhDs as a respected international scholar, he weaves together a self-critical historiography of a twentieth-century Germany that was wrestling with the responsibility for war and genocide. This self-reflexive work explores a wide range of topics including the development of German historiography and methodological debates, the interdisciplinary teaching efforts in German studies, and the development of scholarly organizations and institutions"
Keywords: Jarausch, Konrad -- 1941-; Geschichte 1945-2021; Geschichtsschreibung; Deutschland; Jarausch, Konrad Hugo / author; Germany / Historiography / 20th century; Germany / Study and teaching / History / 20th century; Germany / History / 20th century; Holocaust, Jewish (1939-1945) / Historiography; Historians / Germany / Biography; Historians / United States / Biography; Jarausch, Konrad Hugo; Education; Historians; Historiography; Germany; United States; 1900-1999; Biographies; History; Autobiografie